Still moving : how to lead mindful change - Rowland, Deborah (John Wiley & Sons, 2017)
Still Moving: How to Lead Mindful Change sets out an innovative approach for guiding organisations and indeed entire systems through ongoing, disruptive change. It combines Deborah Rowland's own rigorous research into change and its leadership with insights from her extensive field experience helping major global corporations including GlaxoSmithKline, RWE and Shell achieve lasting change with increased productivity, employee engagement and responsible societal impact. It is filled with helpful inspiring stories of leadership and change from the real world and, bravely, the author's own personal journey. Challenging leaders to cultivate both their inner and outer skills necessary for success, Still Moving weaves together the "being" and "doing" of states of leading change and emphasises the importance of a mindful stance and deep systemic perception within a leader. With the goal of collaborative, sustainable change, the book delves into a variety of important topics, including present-moment awareness, intentional response, edge and tension and emergent change. Compelling and provocative, Still Moving questions the conventional wisdom of much change theory and asks that leaders first work on their inner source in order to more effortlessly change the world around them. --Book Jacket.